Distal into Proximal (Dipr): A homoeotic mutation of Drosophila melanogaster. - Kerridge, S. (Molecular and General Genetics, 1981)
The morphology and genetical characteristics of a new dominant homoeotic mutation, called Distal into proximal (Dipr), are described. Dipr causes two main abnormalities, both of which are specific to distal regions of the adult appendages (i.e. the wing, haltere, legs, antenna, and proboscis); first that distal parts are reduced in size and second that the patterns found distally resemble those normally localised in more proximal parts. The mutation maps to the right arm of chromosome 3 and is associated with an inversion with breakpoints in 84D and 84F. Analysis of revertants of Dipr show that the right breakpoint of In(3R)Dipr is the one responsible for the mutant phenotype. Complementation analyses of Dipr revertants and dosage studies of Dipr with different doses of Dipr+ indicate that the mutant is a hypermorph affecting the normal expression of a gene localised in 84F. The developmental significance of the mutation is discussed.